2022
DOI: 10.1111/jne.13128
|View full text |Cite
|
Sign up to set email alerts
|

Androgen synthesis inhibition increases behavioural flexibility and mPFC tyrosine hydroxylase in gonadectomized male rats

Abstract: Behavioural flexibility is essential to adapt to a changing environment and depends on the medial prefrontal cortex (mPFC). Testosterone administration decreases behavioural flexibility. It is well known that testosterone is produced in the gonads, but testosterone is also produced in the brain, including the mPFC and other nodes of the mesocorticolimbic system. It is unclear how testosterone produced in the brain versus the gonads influences behavioural flexibility. Here, in adult male rats, we assessed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…However, more direct measurements of estrogen levels would be beneficial for more straightforward investigations of the effects of estrogen on task performances. In addition, as testosterone has been also shown to impact performance in cognitive flexibility tasks (Wallin and Wood, 2015 ; Tomm et al, 2022 ), and testosterone levels can vary by individuals (Viau, 2002 ), measurements or experimental designs with testosterone could add more insights into the understanding of sex differences in cognitive flexibility (Shansky, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more direct measurements of estrogen levels would be beneficial for more straightforward investigations of the effects of estrogen on task performances. In addition, as testosterone has been also shown to impact performance in cognitive flexibility tasks (Wallin and Wood, 2015 ; Tomm et al, 2022 ), and testosterone levels can vary by individuals (Viau, 2002 ), measurements or experimental designs with testosterone could add more insights into the understanding of sex differences in cognitive flexibility (Shansky, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, understanding the neural circuits of cognitive flexibility would provide more clarity as to how sex differences in behavior are mediated. Previous research has indicated the importance of dopaminergic input on cognitive flexibility (Floresco et al, 2008 ; Haluk and Floresco, 2009 ; Klanker et al, 2013 ; Radke et al, 2019 ; Tomm et al, 2022 ); as orexin neurons project to the VTA (Peyron et al, 1998 ), understanding how these neural substrates interact could provide more clarity on sex differences in cognitive flexibility after stress. Furthermore, future research should more directly determine the role of gonadal hormones in these circuits, which would lead to a more comprehensive understanding of sex differences in cognitive flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testosterone and its active, nonaromatizable metabolite, dihydrotestosterone (DHT), are synthesized in both the testes (O'Donnell et al, 2022) and the brain (Brandt et al, 2020; Fester & Rune, 2021) including the medial prefrontal cortex and other nodes of the mesocorticolimbic system (Tomm et al, 2022). Circulating testosterone can bind and activate the classical nuclear ARs directly or indirectly through DHT (McEwan & Brinkmann, 2000).…”
Section: Androgensmentioning
confidence: 99%
“…T also participates in the excitatory and inhibitory processes of sexual functions, modulating the activity of neurotransmitter systems, especially dopaminergic (Jordan et al, 2011a; Bell & Sisk, 2013) and opioid peptides (Sharp et al, 2022). Recently, it has been observed that T neurally‐produced increased dopamine signalling in the mesocorticolimbic system (Tomm et al, 2022) and in the extrapyramidal system (Przybylska et al, 2021).…”
Section: Androgensmentioning
confidence: 99%